2020
DOI: 10.1042/bsr20191544
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress modulates differential response in skin fibroblast cells of native cattle (Bos indicus) and riverine buffaloes (Bubalus bubalis)

Abstract: Heat stress in hot climates is a major cause that negatively affects dairy animals, leading to substantial economic loss. The present study was aimed to analyze the effect of heat stress on cellular and molecular levels in dermal fibroblast of cattle and buffaloes. Primary fibroblast culture was established using ear pinna tissue samples of cattle (Bos indicus) and riverine buffaloes (Bubalus Bubalis). The cells were exposed to thermal stress at 42°C for 1 h and subsequently allowed to recover and harvest at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 49 publications
1
11
1
Order By: Relevance
“…Subsequently, Kishore et al [ 39 ] reported higher expression of HSP40 transcript in Holstein Friesian, compared to Sahiwal cows, during summer HS [ 37 ]. After a short-term HS (2 h) exposure, Shandilya et al [ 40 ] also reported induced mRNA expression of HSP40 and HPS70 in fibroblasts of zebu cattle. Taken together, the increase in miRNA expression in the HTHH group, compared to the LTLH group, in this study can be explained.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Kishore et al [ 39 ] reported higher expression of HSP40 transcript in Holstein Friesian, compared to Sahiwal cows, during summer HS [ 37 ]. After a short-term HS (2 h) exposure, Shandilya et al [ 40 ] also reported induced mRNA expression of HSP40 and HPS70 in fibroblasts of zebu cattle. Taken together, the increase in miRNA expression in the HTHH group, compared to the LTLH group, in this study can be explained.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, extracellular vesicles (EVs) released from heat-stressed GCs in the culture media were found to be enriched in miR-1246 compared to EVs from the unstressed cells [ 15 ]. On the other hand, cattle and buffalo fibroblast cells exhibited a reduction in miR-1246 expression in the first few hours after the recovery from exposure to heat stress [ 11 ]. Additionally, the inhibition of miR-1246 improves the viability of retinal pigment epithelial cells after exposure to oxidative stress [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we analyzed the expression pattern of miR-181a and miR-27b in the different GC groups. Both miRNAs are known to be involved in heat stress and immune responses in cattle and buffalo [ 11 , 42 ]. In this study, miR-181a and miR-27b exhibited a similar pattern to miR-1246, with a more than twofold reduction in GCs cultured at 40.5 °C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the HSP protein family, the HSP70 proteins have the most sensitive response to changes in environmental temperature [7]. In cattle the relationship between gene expression and heat stress have been studied for the HSP60, HSP70 and HSP90 genes in Bos taurus indicus [8,9,10,11,12] and Bos taurus taurus [5,13]. Despite to the progress of research in this topic, only one report in Simmental cattle have been published on the regulation of expression of HSP70 gene but, none on the regulation of expression of HSP60 and HSP90 genes under heat stress.…”
Section: Introductionmentioning
confidence: 99%